HUBUNGAN PEMAHAMAN AKIDAH AKHLAK DENGAN PERILAKU SOPAN SANTUN SISWA TERHADAP GURU MTs AL-HIDAYAH INDRAGIRI HULU - Isti Khotimah Ulfiah; Denny Wahyuni; Nur Zakiyah (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2026)
In general, understanding the learning material of Akidah Akhlak leads to changes in behavior towards the better, such as being able to behave politely towards teachers, parents, and friends. However, many students are found to pay less attention to manners and politeness in social life towards others, especially towards older people. Students' respect for teachers seems to fade, where they no longer consider teachers as role models who should be respected and honored. The purpose of this study is to analyze the relationship between the understanding of Akidah Akhlak and students' polite behavior towards teachers of class VIII MTs Al-Hidayah Indragiri Hulu. This study uses a quantitative method with a correlation approach. The sampling technique used is saturated sampling, namely all 87 students of class VIII MTs Al-Hidayah. Data were collected through multiple-choice tests with the intention of knowing the understanding of Akidah Akhlak and questionnaires to measure students' polite behavior towards teachers. Data were analyzed using SPSS 18 with a correlation value of 0.408. The results of the study indicate a positive relationship between students' understanding of Aqidah and Akhlak and their polite behavior towards teachers, with a correlation between the two variables ranging from 0.40 to 0.70, categorized as moderate. The contribution of the relationship is 16.6%, with the remaining 83.4% determined by other factors.